Are sputum eosinophils associated with a different phenotype in COPD patients? A retrospective study. (December 2021) - Bartoli, Maria Laura; Latorre, Manuela; Vagaggini, Barbara; Nieri, Dario; Cianchetti, Silvana; Di Franco, Antonella; Celi, Alessandro; Paggiaro, Pierluigi
Abstract: Sputum eosinophilia in Chronic Obstructive Pulmonary Disease (COPD) patients seems to be associated with a better response to inhaled corticosteroids (ICS). To verify if this feature could identify a specific subpopulation of COPD patients, we retrospectively compared functional and inflammatory parameters of 110 COPD patients according to the presence of sputum eosinophilia (>2%). Patient with eosinophilia were characterized by lower dyspnea score, lower functional impairment and lower ICS use, suggesting that airway eosinophilia may be associated to a lower COPD severity and some functional "asthma-like" characteristics, therefore explaining the better response to ICS in this subgroup of patients. Highlights: - Sputum eosinophils, seldom measured in COPD patients, may offer useful informations. - Sputum eosinophilia is associated with lower level of COPD severity. - COPD patients with sputum eosinophilia have a prominent "bronchiolitic" phenotype. - They are less frequently treated with ICS, but may receive some advantage from them.